Solubilization and Upgrading of High Polyethylene Terephthalate Loadings in a Low‐Costing Bifunctional Ionic Liquid. Issue 4 (26th January 2018) - Sun, Jian; Liu, Dajiang; Young, Robert P.; Cruz, Alejandro G.; Isern, Nancy G.; Schuerg, Timo; Cort, John R.; Simmons, Blake A.; Singh, Seema
Abstract: The solubilization and efficient upgrading of high loadings of polyethylene terephthalate (PET) are important challenges, and most solvents for PET are highly toxic. Herein, a low‐cost (ca. 1.2 kg −1 ) and biocompatible ionic liquid (IL), cholinium phosphate ([Ch]3 [PO4 ]), is demonstrated for the first time to play bifunctional roles in the solubilization and glycolytic degradation of PET. A high loading of PET (10 wt %) was readily dissolved in [Ch]3 [PO4 ] at relatively low temperatures (120 °C, 3 h) and under water‐rich conditions. In‐depth analysis of the solution revealed that high PET solubilization in [Ch]3 [PO4 ] could be ascribed to significant PET depolymerization. Acid precipitation yielded terephthalic acid as the dominant depolymerized monomer with a theoretical yield of approximately 95 %. Further exploration showed that in the presence of ethylene glycol (EG), the [Ch]3 [PO4 ]‐catalyzed glycolysis of PET could efficiently occur with approximately 100 % conversion of PET and approximately 60.6 % yield of bis(2‐hydroxyethyl)terephthalate under metal‐free conditions. The IL could be reused at least three times without an apparent decrease in activity. NMR spectroscopy analysis revealed that strong hydrogen‐bonding interactions between EG and the IL played an important role in the activation of EG and promotion of the glycolysis reaction. This study opens up avenues for exploring environmentally benign and efficient IL technology for solubilizing and recycling postconsumer polyester plastics. Abstract : No PETs allowed : A low‐cost (ca. 1.2 kg −1 ) biocompatible ionic liquid (IL), cholinium phosphate ([Ch]3 [PO4 ]), can play bifunctional roles in the solubilization and efficient glycolytic upgrading of high polyethylene terephthalate (PET) loadings, which opens up avenues for exploring environmentally benign and sustainable technology for solubilizing and recycling postconsumer polyester plastics.